Letter to the Editor in response to: Important knowledge for parents of children with heart disease: parent, nurse, and physician views - Tallon, Mary; Kendall, Garth; Newall, F. (CAMBRIDGE UNIV PRESS, 2017)
LETTER TO THE EDITOR